PENGARUH VOLATILITAS LABA, KEBIJAKAN DIVIDEN, DAN LEVERAGE TERHADAP VOLATILITAS HARGA SAHAM IDX30 - Rosita Putri Cahyawati; Munasiron Miftah (Jurnal Riset Akuntansi dan Keuangan, 2022)
This quantitative research is intended to find out the effect of earnings volatility, dividend policy, and leverage on stock price volatility. The population is the IDX30 index company on the Indonesia Stock Exchange from 2012 to 2019. The sampling method used when conducting the research is non-probability sampling with a saturated sample so that a total sample of 30 companies is obtained. Data analysis used the Microsoft Office Excel 2019 computer program and the E-Views 11 program with a significance level of 0.05 or 5%, then the method used for hypothesis testing was the panel data regression analysis method. The results of the test are (1) there is an effect between earnings volatility and stock price volatility, (2) there is an influence between dividend policy and stock price volatility, (3) there is an influence between leverage and stock price volatility.Keywords. Dividend Policy; Earnings Volatility; Leverage; Stock Price Volatility